High Neutrophil-To-Lymphocyte Ratio (NLR) and Systemic Immune-Inflammation Index (SII) Are Markers of Longer Survival After Metastasectomy of Patients With Liver-Only Metastasis of Rectal Cancer - Nándor Polk; Barna Budai; Erika Hitre; Attila Patócs; Attila Patócs; Attila Patócs; Tamás Mersich (Frontiers Media S.A., 2022)
Background: The literature data regarding colon cancer patients with liver-only metastases (CLM) show that NLR determined before metastasectomy is a prognostic marker of shorter relapse-free survival (RFS), but no results has been reported to date for rectal cancer patients with liver-only metastases (RLM). This study aimed to investigate the NLR and SII in CLM and RLM.Methods: Relapse-free (RFS) and overall survival (OS) were evaluated in 67 CLM and 103 RLM patients with a median follow-up of 46.5 and 59.8 months, respectively. Pre- and/or postoperative chemotherapy ± targeted treatment was applied in 96% and 87% of CLM and RLM patients, respectively. The cut-off level for hematologic parameters were determined by receiver operating characteristic (ROC) analysis. Univariate analysis was performed by Kaplan-Meier method and log rank test. For multivariate analysis Cox regression was applied.Results: In univariate analysis low NLR (cut-off 2) and SII (535) were predictors of longer RFS in case of CLM (p < 0.01). In contrast, for RLM high NLR (2.42) and SII (792) were predictors of longer RFS (p < 0.001). For RLM both NLR and SII proved to be independent markers of RFS (HR 0.66 (95% CI 0.52-0.84) and 0.73 (0.57-0.91), respectively) and OS (0.76 (0.58-0.99) and 0.66 (0.5-0.87), respectively). Only NLR (1.44 (1.04-1.99)) was independent marker of RFS for CLM. The preoperative treatment has not influenced the role of NLR or SII.Conclusion: In contrast to CLM, in RLM the high NLR or SII determined before metastasectomy proved to be independent prognostic factors of longer RFS and OS.